Deepening Linkages Between South Asia and Southeast Asia : Synthesis Report - World Bank (Washington, DC, 2022)
Although economic linkages between South Asia and Southeast Asia have been strengthened over the past decade, integration between these two regions remains limited. Can new approaches to regional integration help revitalize trade and economic links between South Asia and Southeast Asia This report looks at new approaches to strengthen trade and revitalize economic links between South Asia and Southeast Asia. It documents the emerging trade, investment, and migration trends between the two regions. The report explores the current constraints that limit the links between South Asia and Southeast Asia, discusses the expected gains from their removal, and provides recommendations on advancing regional integration to policy makers in both regions. The main objective of this report is to look at new approaches to strengthen trade and revitalize economic links between South Asia and Southeast Asia. Section 1 documents the emerging trade, investment, and migration trends between South Asia and Southeast Asia, with particular focus on digital and environmental goods and services. Section 2 explores the current constraints that limit the links between the two regions, and section 3 discusses the expected gains from their removal. Section 4 concludes with recommendations on advancing regional integration between South Asia and Southeast Asia.